1970
DOI: 10.1021/jf60169a014
|View full text |Cite
|
Sign up to set email alerts
|

Excretion, distribution, and tissue storage of a carbon-14-labeled photoconversion product of 14C-dieldrin

Abstract: Subacute levels ( 5 pg per day) of 14C-labeled dieldrin or photodieldrin were administered to young adult rats of both sexes for as long as 12 weeks. Photodieldrin was given both orally and intraperitoneally ; dieldrin was given by stomach tube only. Urinary, fecal, and total excretion patterns as well as tissue distribution and storage of 'T-labeled residues were determined. From 59.2 to 64.7z of the 14C-activity administered as photodieldrin was excreted in the urine and feces of male rats and 45.9 to 49.0 z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

1975
1975
1990
1990

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 4 publications
3
9
0
Order By: Relevance
“…Acetone extracts of feces during the period of study did not show even trace amounts of radioactivity at any time, suggesting that the disposition of photoheptachlor takes place exclusively through the kidneys. This mode of excretion resembles that reported for photodieldrin in rabbit and monkey (Reddy and Khan, 1975;Nohynek et al, 1978) but differs from that of photodieldrin in rat (Dailey et al, 1970) where the major part of the label is passed through feces. It should, however, be pointed out that complete absence of radioactivity in feces of rabbits treated with [14C] photoheptachlor may be due to two reasons:…”
Section: Resultssupporting
confidence: 68%
“…Acetone extracts of feces during the period of study did not show even trace amounts of radioactivity at any time, suggesting that the disposition of photoheptachlor takes place exclusively through the kidneys. This mode of excretion resembles that reported for photodieldrin in rabbit and monkey (Reddy and Khan, 1975;Nohynek et al, 1978) but differs from that of photodieldrin in rat (Dailey et al, 1970) where the major part of the label is passed through feces. It should, however, be pointed out that complete absence of radioactivity in feces of rabbits treated with [14C] photoheptachlor may be due to two reasons:…”
Section: Resultssupporting
confidence: 68%
“…Therefore, studies of its metabolism in various animals are of significant importance. Limited studies of the in vivo metabolism and distribution of photodieldrin in rats (Dailey et al, 1970;Klein et al, 1970;Dailey et al, 1972) and in vitro metabolism by mixed-function oxidase of various animals (Reddy and Khan, 1974) revealed that there was a species and sex difference in its metabolism. As photolysis of aldrin and dieldrin occurs on plant surfaces the effect of photodieldrin on herbivorous animals is of ecological significance.…”
mentioning
confidence: 99%
“…Photodieldrin, an environmental "terminal residue" of the commonly used insecticides aldrin and dieldrin (Rosen et al, 1966;Khan et al, 1974), is considerably persistent in the environment (Suzuki et al, 1974;Reddy and Khan 1975a). It is metabolized by some insects (Khan et al, 1969; Reddy and Khan, 1977) and mammals (Klein et al, 1969(Klein et al, , 1970(Klein et al, , 1973Dailey et al, 1970Dailey et al, , 1972Khan, 1974, 1975b) to lipophilic and hydrophilic metabolites. Oral and intraperitoneal treatment of male rabbits resulted in excretion of about 50% (55% when intraperitoneally and 48.5% when orally administered) of the administered dose in urine and only 3% in feces in 9 days (Reddy and Khan, 1975b).…”
Section: Urinary Metabolites Of [14c]photodieldrin In Male Rabbitsmentioning
confidence: 99%